Efficacy and safety of the use of non-vitamin K antagonist oral anticoagulants in patients with nonvalvular atrial fibrillation and concomitant Aspirin therapy: a meta-analysis of randomized trials - Bennaghmouch, Naoual; Brückmann, Martina (Circulation, 2018)
Background: Current guidelines recommend non-vitamin K antagonist oral anticoagulants (NOACs) as the first-choice therapy in patients with nonvalvular atrial fibrillation because these drugs have several benefits over the vitamin K antagonists (VKAs). It is unknown whether these benefits remain when NOACs have to be combined with aspirin therapy. To assess the efficacy and safety of NOACs compared with VKAs in patients with atrial fibrillation and concomitant aspirin therapy, we conducted a systematic review and study-based meta-analysis of published randomized controlled trials.
Gesehen am 11.04.2018